Epidemiological Trends and Clinicomycological Profile of Chronic Dermatophytosis: A Descriptive Study From South India - Remya Rajamohanan; Renu Raj; Janaki Chellam; Madhu Rengasamy (Wolters Kluwer Medknow Publications, 2021)
Background: Chronic dermatophytosis refers to persistent or recurrent episodes of dermatophytosis lasting for more than 1 year despite adequate treatment with topical and systemic antifungal agents. The rise in the number of these cases is alarming over the past 5 to 6 years, and a thorough knowledge about the reasons for chronicity of dermatophytosis may go a long way in the treatment and prevention of this infection. Aims and Objectives: The aim of this study was to investigate the epidemiology, various clinical types, and factors associated with chronicity in patients with chronic dermatophytosis, and to isolate the etiological agents and study the clinicomycological correlation. Materials and Methods: Detailed history and clinical details of all patients with chronic dermatophytosis who presented to our tertiary care center over a span of 1 year were recorded. Skin scrapings from these patients were subjected to potassium hydroxide mount and culture in modified Sabouraud's dextrose agar medium. Results: Sixty-four patients were enrolled in this study with a mean age of 44.5 years. The mean duration of infection was 3.14 years. Tinea corporis was the most common clinical type seen in 46 (71.9%) patients, affecting commonly the waist area in females and the back in males. Bronchial asthma was the most frequent systemic association affecting 20 (31.3%) patients followed by diabetes mellitus, which was present in 13 (20.3%) patients. About 34% patients had a history of long-term steroid use. Among the 28 isolates, Trichophyton mentagrophytes was the most frequent species isolated (46.4%), followed by Trichophyton rubrum (39.3%). Trichophyton tonsurans and Trichophyton verrucosum were isolated from two patients each. Conclusion: Extensive area of involvement, atopy, diabetes, and long-term use of systemic corticosteroids were associated with chronicity. Unlike in the yesteryears, T. mentagrophytes has emerged as the most common etiological agent of chronic dermatophytosis.